2022
DOI: 10.1039/d1cp05130j
|View full text |Cite
|
Sign up to set email alerts
|

Surface sensitive infrared spectroelectrochemistry using palladium electrodeposited on ITO-modified internal reflection elements

Abstract: Palladium nanoparticles have been electrodeposited on the surfaces of conductive indium tin oxide (ITO) modified silicon internal reflection elements. The resulting films are shown to be excellent platforms for attenuated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 59 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…However, relatively thick films of the second metal are required to ensure that the resulting surface is free of pinhole defects, which compromises the optimal SEIRAS activity of the interface. In recent years, we have promoted the use of conductive metal oxides (CMOs) as a base layer for ATR-SEIRAS and reported that such materials are infrared transparent yet conductive, allowing metal nanoparticle films to be directly electrodeposited on thin (∼20 nm) CMO films coated on the surface of an IRE. , Metal on CMO modified IREs was shown to give strong ATR-SEIRAS signals and is far more robust in electrochemical environments compared to metal films directly deposited on IRE surfaces. , …”
Section: Resultsmentioning
confidence: 99%
“…However, relatively thick films of the second metal are required to ensure that the resulting surface is free of pinhole defects, which compromises the optimal SEIRAS activity of the interface. In recent years, we have promoted the use of conductive metal oxides (CMOs) as a base layer for ATR-SEIRAS and reported that such materials are infrared transparent yet conductive, allowing metal nanoparticle films to be directly electrodeposited on thin (∼20 nm) CMO films coated on the surface of an IRE. , Metal on CMO modified IREs was shown to give strong ATR-SEIRAS signals and is far more robust in electrochemical environments compared to metal films directly deposited on IRE surfaces. , …”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we incorporate a conductive layer of indium tin oxide (ITO) beneath thin plasmonic Au. This approach has previously been demonstrated for FTIR applications and more recently for 2D IR. , We choose to use ALD to fabricate the ITO layer due to the atomic level control that it provides via self-limiting growth and its ability to grow high-quality, low-resistivity thin films . By separating the plasmonic material from the bulk conductor of the electrode, we are able to separately optimize each layer.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that the plasmon peak of ITO can be tuned from ∼5000 to ∼3000 cm –1 via adjusting its dopant level. , The LSPR resonance is closely related to the free electrons produced by introducing a foreign atom of Sn 4+ into the matrix of In 2 O 3 as n-type doping, which can be further explained by the modified Drude model . Due to its tunability in the infrared region, ITO has great potential in the fields of infrared reflection material, infrared stealth material, infrared manipulation, thermal shielding coating, , and smart glass. Although ITO has been widely used for applications concerned with infrared, to the best of our knowledge, the research of ITO’s LSPR and its coupling effect in infrared reflection enhancement is still at large.…”
Section: Introductionmentioning
confidence: 99%